Treatment of wool fibres with subtilisin and subtilisin-PEG - Silva, Carla J. S. M. (2005)
In this work the diffusion of serine proteases into wool fabrics and yarns was studied. The proteases used were free subtilisin and subtilisin-PEG (the same enzyme that was covalently cross linked to polyethylene glycol). It is shown that the adsorption and diffusion is facilitated by the pre-treatment performed, being the alkaline surfactant washing and bleaching the most effective in what concerns enzyme adsorption. Furthermore, this study suggests that the diffusion of proteases into wool is dependent on the size of the protease. The free enzyme penetrates into wool fibre cortex while the modified bigger enzyme is retained only at the surface, in the cuticle layer. Also, proteins without proteolytic activity do not adsorb considerably on wool due to its hydrophobic nature, therefore the diffusion is facilitated by hydrolytic action. These results have important practical implications for the establishment of enzymatic wool finishing processes, since they allow for control of the enzyme hydrolysis, which was the major drawback of this environmental friendly option to the conventional chlorine treatments.